Impact of natural menopause on multiple sclerosis: a multicentre study. Issue 11 (12th June 2019) - Baroncini, Damiano; Annovazzi, Pietro Osvaldo; De Rossi, Nicola; Mallucci, Giulia; Torri Clerici, Valentina; Tonietti, Simone; Mantero, Vittorio; Ferrò, Maria Teresa; Messina, Maria Josè; Barcella, Valeria; La Mantia, Loredana; Ronzoni, Marco; et al.
Abstract : Objective: To study the effect of natural menopause on multiple sclerosis clinical course. Methods: This was an observational, retrospective, multicentre, cohort study. Menopause onset was defined by the final menstrual period (FMP) beyond which no menses occurred for 12 months. We included multiple sclerosis (MS) patients with FMP occurred after 2005 and a recorded follow-up of at least 2 years pre-FMP and post-FMP. We excluded patients with primary progressive course, iatrogenic menopause and with other confounders that could mask menopause onset. We compared relapse-rate and expanded disability status scale (EDSS) scores pre-FMP and post-FMP, searching for possible interactions with age, disease duration, cigarette smoking and nulliparity status. Results: 148 patients were included (mean observation: 3.5 years pre-FMP and post-FMP). Most patients (92%) received disease-modifying therapies, mainly first-lines. After menopause the annualised relapse rate (ARR) significantly decreased (from 0.21±0.31 to 0.13± 0.24; p=0.005), while disability worsened (increase of mean 0.4 vs 0.2 points after menopause; p<0.001). Older age and long-lasting disease were associated with ARR reduction (p=0.013), but not with disability worsening. Cigarette smokers showed a trend to a higher disability accumulation after menopause (p=0.059). Conclusion: Natural menopause seems to be a turning point to a more progressive phase of MS. Relapse rate is also reduced after menopause, but this effect could be driven most by ageing and shifting to progressive phase in patients with long-lasting disease. Cigarette smoking could speed up disability progression after menopause.